Prosthodontic Rehabilitation of the Patient with Severely Worn Dentition: A Case Report. (9th July 2012) - Hatami, Mahnaz; Sabouhi, Mahmoud; Samanipoor, Siamak; Badrian, Hamid
Abstract : The management of tooth wear has been a subject of increasing interest from both preventive and restorative points of view. This paper describes the full mouth rehabilitation of a 63-year-old bruxer man with a severely worn dentition and other dental problems including unsuitable restorations and several missing teeth. The treatment entailed using cast posts and cores, metal-ceramic restorations, and a removable partial denture. As with the treatment procedure of such cases, equal-intensity centric occlusal contacts on all teeth and an anterior guidance in harmony with functional jaw movements were especially taken into account.